Assessment of potentially toxic element contents in chickens and poultry feeds from Bangladesh markets: Implications for human health risk - Shamim Al Mamun; Mohammad A. Islam; Shamshad B. Quraishi; Mohammad M. Hosen; Brett H. Robinson; Ismail M.M. Rahman (Toxicology Reports)
Chicken (Gallus domesticus) is a significant source of animal protein for the people of Bangladesh. However, anthropogenic activity may contaminate chicken meat with potentially toxic elements (PTEs) despite the nutritional benefits. Current work aims to determine the accumulated content of PTEs (Pb, Cd, Cr, As, and Hg) in chickens and poultry feeds commercially sold in Bangladesh markets and compare with WHO, FAO, EU, EC, FSANZ standards. Three different chicken varieties, native (local variety, freehand raised), poultry (raised for meat only), and layer chicken (commercially raised for eggs and later used for meat), were investigated, and commercial poultry feeds were used to raise the latter two varieties. The Pb, Cd, Cr, As, and Hg contents (mg kg–1 fresh weight (f.w.) were 0.481–1.067, 0.025–0.118, 0.069–0.319, 0.007–0.071, 0.002–0.019, respectively. In addition, associated health risks due to the PTEs in different varieties of chicken organs, e.g., meat, liver, and kidney, were evaluated. The study suggests that the poultry feeds should be carefully monitored regarding PTEs content to avoid potential human health risks due to chicken consumption in Bangladesh.